Antigones of contemporary theatre: capturing problems of today’s civil disobedience in a theatre play - Dorota Anna Gozdecka (Law Text Culture, 2021)
Despite its ancient origin Sophocles’ Antigone has proven to be timeless and provided continued inspiration for legal scholars, theatre practitioners and theorists alike. In this article I reflect on how the figure of Antigone continues to inspire contemporary play writing preoccupied with the intersections of law and theatre. The article analyses the play of my authorship, ‘Trumpsformation’ using the notion of ‘contemporary Antigones’. I argue that while Antigone has been often seen as a specific type of a female character, sometimes even a disturbed one, in my understanding a variety of characters can take on a role of an Antigone. This is possible, because Antigone’s political power lies in her role as a dissident who challenges injustices perpetuated in the name of the law. In this article I show how the presence of the figure of a contemporary Antigone and the use of an Antigonean conflict can be incorporated in the process of staging contemporary stories about injustice, law and the ethical duty in the times of conflict over the shape of political community.